2021
DOI: 10.1080/03057240.2020.1862073
|View full text |Cite
|
Sign up to set email alerts
|

What does character education mean to character education experts? A prototype analysis of expert opinions

Abstract: Having an agreed-upon definition of character education would be useful for both researchers and practitioners in the field. However, even experts in character education disagree on how they would define it. We attempted to achieve greater conceptual clarity on this issue through a prototype analysis in which the features perceived as most central to character education were identified. In Study 1 (N = 77), we asked character education experts to enumerate features of character education. Based on these lists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
1
21
0
10
Order By: Relevance
“…Implementasi perenting permisif dapat mengakibatkan anak sekolah kurang memiliki kontrol diri serta melakukan perlakuan semaunya dan merasakan bukan bagian penting orangtuanya (Wana, 2019). Penanaman moral merupakan bagian utama sesorang dalam mengandung nilai, kepastian, kapasitas perilaku, serta kekuatan untuk menantang dari kesulitan (McGrath et al, 2022). Selanjutnya karakter identik dengan moral dan etika, karakter dari nilai-nilai perilaku masyarakat universal yaitu semua kegiatan masyarakat, hubungan dengan Tuhan, dirinya, dan sesama manusia, serta lingkungan sekitarnya (Haslip & Haslip, 2013).…”
Section: Pola Asuh Permisif Terhadap Pembentukan Karakterunclassified
“…Implementasi perenting permisif dapat mengakibatkan anak sekolah kurang memiliki kontrol diri serta melakukan perlakuan semaunya dan merasakan bukan bagian penting orangtuanya (Wana, 2019). Penanaman moral merupakan bagian utama sesorang dalam mengandung nilai, kepastian, kapasitas perilaku, serta kekuatan untuk menantang dari kesulitan (McGrath et al, 2022). Selanjutnya karakter identik dengan moral dan etika, karakter dari nilai-nilai perilaku masyarakat universal yaitu semua kegiatan masyarakat, hubungan dengan Tuhan, dirinya, dan sesama manusia, serta lingkungan sekitarnya (Haslip & Haslip, 2013).…”
Section: Pola Asuh Permisif Terhadap Pembentukan Karakterunclassified
“…Based on these various understandings and definitions, it can be concluded that character education is an attempt to introduce and instil character values in students so that students can know, think and act with moral considerations in making decisions or facing problems. Character education is carried out so that a person can identify problems, think and act by considering values and norms (McGrath et al, 2022;Paul et al, 2020). The character education programme designed by the researcher is to combine teacher professional development and student character development.…”
Section: Character Educationmentioning
confidence: 99%
“…Moreover, it has also been recognised that cognitive skills measured by achievement tests are not the only determinant of individual quality. Non-cognitive factors are related to emotional and social (Hadianto et al, 2021b;McGrath et al, 2022;Qoyyimah, 2016). The term 'non-cognitive skills' is used by scientists for various traits believed to be different from skills measured by IQ tests and achievement tests, such as personality or character, motivation or interests.…”
Section: Cognitive Non-cognitive Competencies and Teacher Competenciesmentioning
confidence: 99%
“…Character education is a genuine effort to help a person understand, care, and act based on ethical values. 12 It can also be interpreted as a deliberate growing discipline and attempt to develop students' ethical behaviors at school and become an everyday opportunity. The crucial elements of character education that should be optimized for students are respect, truth, fairness, and responsibility.…”
Section: Introductionmentioning
confidence: 99%